Como a sazonalidade afeta a distribuição e diversidade de comunidades vegetais na Zona de Transição Aquático-Terrestre em lagoas marginais? - Milhomens, Larissa Bezerra Soares (2022)
The construction of dams in floodplains can change the characteristics of aquatic environments, affecting the structure and dynamics of the plant community. The aim of this study was to evaluate the effect of perennialization and seasonality on the structure of the plant community along the flood gradient in seasonal lakes of the Pandeiros river in terms of composition, richness and life forms. This work was carried out in four lakes, where three did not undergo perennialization and one was perennialized. In each lake, permanent 30 m long transects were established, divided into four levels (aquatic, wet, flood, and terrestrial). In each transect, continuous plots of 1 m² were launched, where composition, vegetation cover, richness, limnological data (pH, depth, dissolved oxygen, temperature and electrical conductivity) and soil fertility data were collected. A rarefaction curve was used to assess differences in species richness between lakes and between quotas. To assess the floristic dissimilarity between the ponds and verify whether the composition varied seasonally and along the gradient, non-metric multidimensional scaling (NMDS) was used, followed by Similarity Analysis (ANOSIM) and Percentage Similarity Analysis (SIMPER). To assess which environmental variables influenced species richness and composition, generalized linear models (GLMs) and redundancy analysis (RDA) were used, respectively. The perennial lake presented greater richness (S = 142 spp.) than the non-perennial lakes (S = 115 ssp.), in both areas greater richness was observed in the terrestrial level when compared to the flooded part of the gradient. Composition varied seasonally in both study areas and along the flood gradient (p < 0.05). The richness of the perennial pond was influenced by the concentration of phosphorus in the soil, while that in the non-perennial ponds was influenced by the organic matter content, water pH and sum of bases. Regarding the floristic composition, in the perennial lake in both periods it was influenced by the concentration of phosphorus, organic matter, depth and sum of bases. While in non-perennial lakes only the composition observed during the rainy season was influenced by environmental variables (depth, dissolved oxygen and temperature). The hemicryptophyte and therophyte life forms were dominant throughout the study in both the perennial and non-perennial lakes. Thus, it was concluded that the seasonal variation in the hydrological cycle and the concentration of soil nutrients are the main factors that influence the richness and floristic composition of vegetation in perennial and non-perennial lakes of the Pandeiros River.